Digital Support for Indigenous Language Revitalization Efforts in Kamchatka: The "Koryak Tuyu" Mobile Application for Koryak Language Learning. - Fayzrakhmanova, Yulia S. (Sibirica: Interdisciplinary Journal of Siberian Studies)
This article focuses on the revitalization of the Koryak language, one of the seven Indigenous languages in Kamchatka, Russia. It begins by framing the ethnolinguistic situation in Kamchatka in the context of demographic and statistical data, and continues with an overview of efforts to preserve and develop endangered Indigenous languages in the region. It then introduces the uptake of digital technology for Koryak language learning. To support technology inclusion with remote communities, a mobile language learning application called "Koryak Tuyu" has been developed to facilitate the study of Koryak as a supplemental tool through both home-based individual learning and classroom learning. The article provides a description of the language application and a discussion of the application's features and components.